2021
DOI: 10.1002/art.41585
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Rheumatoid Arthritis by Enhanced Lymph Node Trafficking of Engineered Interleukin‐10 in Murine Models

Abstract: Objective. Rheumatoid arthritis (RA) is a major autoimmune disease that causes synovitis and joint damage. Although clinical trials have been performed using interleukin-10 (IL-10), an antiinflammatory cytokine, as a potential treatment of RA, the therapeutic effects of IL-10 have been limited, potentially due to insufficient residence in lymphoid organs, where antigen recognition primarily occurs. This study was undertaken to engineer an IL-10-serum albumin (SA) fusion protein and evaluate its effects in 2 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…MP-HCQ treatment also exhibited a high anti-inflammatory effect in BMDMs, similar to RAW274.7 cells, with significantly declined IL-6 (** p , *** p ) and inclined IL-10 secretion (Figure b). Studies have shown that the administration of exogenous IL-10 could inhibit the production of inflammatory cytokines in synovial tissues and prevent the production of pro-inflammatory cytokines, such as IL-5, IL-6, and IL-27 . The high IL-10/IL-6 ratio of MP-HCQ-treated BMDMs (Figure b) underlined a highly favorable microenvironment to alleviate the inflammation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…MP-HCQ treatment also exhibited a high anti-inflammatory effect in BMDMs, similar to RAW274.7 cells, with significantly declined IL-6 (** p , *** p ) and inclined IL-10 secretion (Figure b). Studies have shown that the administration of exogenous IL-10 could inhibit the production of inflammatory cytokines in synovial tissues and prevent the production of pro-inflammatory cytokines, such as IL-5, IL-6, and IL-27 . The high IL-10/IL-6 ratio of MP-HCQ-treated BMDMs (Figure b) underlined a highly favorable microenvironment to alleviate the inflammation.…”
Section: Resultsmentioning
confidence: 95%
“…Studies have shown that the administration of exogenous IL-10 could inhibit the production of inflammatory cytokines in synovial tissues and prevent the production of proinflammatory cytokines, such as IL-5, IL-6, and IL-27. 48 The high IL-10/IL-6 ratio of MP-HCQ-treated BMDMs (Figure 2b) underlined a highly favorable microenvironment to alleviate the inflammation. It is noticed that empty polymersome MP did not affect the secretion of these cytokines, and free HCQ had only limited secretion of IL-10.…”
Section: Resultsmentioning
confidence: 96%
“…While the IA agent suppressed arthritis in treated joints, it did not display systemic efficacy. [ 72 ] PLGA‐ATRA MP have the advantage of acting locally at the site of inflammation to promote disease‐specific immunomodulation without a priori knowledge of participating epitopes. Other methods using biomaterial depots to expand T reg have used PLGA microparticles encapsulating multiple immunoregulatory agents, such as rapamycin, IL‐2, and TGF‐ β that, when injected near hind paw draining lymph nodes, modulated disease but also resulted in a systemic immunosuppression and nonspecific expansion of T reg .…”
Section: Discussionmentioning
confidence: 99%
“…However, the complex nature of RA immunopathogenesis is influenced by several intrinsic and extrinsic factors, and the pleiotropic nature of IL-10 makes this aim difficult. The previous clinical trials showed a limited therapeutic effect of IL-10, but the studies continue these days in an attempt to offer a new IL-10-based strategy for RA therapy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping for the -1082A/G polymorphism in the IL10 gene (rs1800896) was performed by an amplification refractory mutation system (ARMS)–PCR assay using a forward primer specific for G allele 5′-CCTATCCCTACTTCCCCC-3′, a forward primer specific for A allele 5′-CCTATCCCTACTTCCCCT-3′ and a reverse generic primer 5′AGCAACCACTCCTCGTCGCAAC-3′. The parameters of thes PCR protocol were the same as described by Miteva et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%